Population Distribution of Indian Giant Squirrel Ratufa indica in Dry and Moist Deciduous Forest of Sironcha forest Division, Central India - Shukla, Prabhu Nath; Mishra, Virendra Kumar (Indian Forester, 2017)
Distribution of the Indian Giant squirrel (IGS), Ratufa indica population was studied in the moist deciduous, dry deciduous forest and moist evergreen forests of Sironcha Forest Division, Maharashtra, India. A total of 2803 nests of IGS were observed including 1533 nests used by the species suggesting 256 individuals. The nests were distributed in clusters and 39% of them occurred in 5 clusters. The nest density ranged between 0.5 and 42.7 km2. Amongst 98 tree species recorded in the area, IGS used 49 species for nest building. IGF build around 71% of its nests on nine tree species. The most preferred tree species was Xylia xylocarpa followed by Terminalia alata, Anogeissus latifolia and Madhuca longifolia. Evergreen trees were preferred for nest building as compared with deciduous trees. The data suggests that even good quality forests with close canopy and high biodiversity are devoid of sizeable IGS population.